Opioid and sedative requirements in extracorporeal membrane oxygenation patients on hydromorphone versus fentanyl. Issue 5 (1st December 2021) - Browder, Kelsey; Wanek, Matthew; Wang, Lu; Hohlfelder, Benjamin
Abstract: Background: The extracorporeal membrane oxygenation (ECMO) circuit causes pharmacokinetic alterations of medications which impact drug selection and dosing. Although hydromorphone has a favorable pharmacokinetic profile, it is unclear whether hydromorphone provides better patient‐centered benefits compared to fentanyl. The objective of this study is to compare opioid and sedative requirements in ECMO patients started on a fentanyl‐ versus hydromorphone‐based analgesia regimen. Methods: This was a non‐interventional retrospective cohort study. It was conducted at a single center in the cardiovascular intensive care units and cardiac intensive care units. We included venovenous (VV) or venoarterial ECMO patients. Patients who were started on a fentanyl continuous infusion within 24 h of cannulation were compared to patients started on a hydromorphone continuous infusion. Results: A linear mixed effects model was performed to compare doses of opioid, sedative, and propofol between groups over time. We included 28 hydromorphone patients and 53 fentanyl patients, with 85% on VV ECMO. There were no differences between hydromorphone and fentanyl groups in opioid or sedative (including propofol and benzodiazepine) doses for any ECMO day ( p value for interaction .63 and .83, respectively). Propofol doses alone, however, were significantly higher in the fentanyl group on ECMO days three, four, and five. Conclusions: There appear to be no major differences in opioid or sedative requirements whether ECMO patients are initiated on a hydromorphone‐ or fentanyl‐based regimen. Abstract : Average Daily Medication Doses During ECMO.